2021
DOI: 10.1007/s13577-021-00542-y
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of long non-coding RNA XIST aggravates sepsis-induced lung injury by regulating miR-16-5p

Abstract: This study aims to explain the role and related mechanisms of long non-coding RNA (lncRNA) X inactive specific transcript (XIST) in sepsis-induced acute lung injury (ALI). The in vivo septic models and in vitro septic model were established. In animal models, the lung injury of the rats was evaluated after XIST was overexpressed. In cell models, the effects of XIST and microRNA (miR)-16-5p on ALI was detected by MTT assay, Western blot and ELISA. The interaction between XIST and miR-16-5p was investigated by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…[ 40 ] Another investigation provided evidence that the long non-coding RNA X inactive specific transcript has the potential to mitigate sepsis-induced acute lung damage by targeting miR-16-5p. [ 41 ] Furthermore, research has shown that the overexpression of miR-16-5p effectively inhibits the inflammatory response via the repression of PIK3R1-mediated activation of the PI3K/Akt/NF-κB pathway to exerting anti-inflammatory effect. [ 42 ] All of these data suggest the importance of miR-16-5p in oxidative stress and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] Another investigation provided evidence that the long non-coding RNA X inactive specific transcript has the potential to mitigate sepsis-induced acute lung damage by targeting miR-16-5p. [ 41 ] Furthermore, research has shown that the overexpression of miR-16-5p effectively inhibits the inflammatory response via the repression of PIK3R1-mediated activation of the PI3K/Akt/NF-κB pathway to exerting anti-inflammatory effect. [ 42 ] All of these data suggest the importance of miR-16-5p in oxidative stress and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-16-5p has been confirmed to play a vital role in sepsis-related diseases (28,29). Song et al revealed that miR-16-5p promoted sepsis-induce lung injury, which enhanced the apoptosis, inflammation, and oxidative stress of LPS-induced airway epithelial cells (30). Importantly, our previous research showed that miR-16-5p was upregulated in septic patients and LPS-treated cells, which might aggravate sepsis process via promoting aerobic glycolysis (31).…”
Section: Discussionmentioning
confidence: 99%
“…TUG1 could also alleviate pulmonary inflammation and lung vascular endothelial cell injury (89). X inactive specific transcript (XIST) was observed to be overexpressed in a lung injury rat model, and the researchers concluded that XIST might ameliorate sepsis-induced lung injury by modulating miR-16-5p (91). Hence, lncRNAs play important roles in sepsis-induced lung injury and they may become new diagnostic and therapeutic biomarkers for lung injury caused by sepsis (Figure 3).…”
Section: Lncrnas In Sepsis-induced Lung Injurymentioning
confidence: 99%